PENANGANAN ABRASI PANTAI PASIR MAYANG - Salamun Salamun (KEAIRAN, 2006)
Seawall or Revetment have been devised to protect coastal or shoreline form  erosion by Waves. The seawall or revetment system must be resist direct wave attack, reduces hydraulic forces on underlying material and constribute to dissipation wave energy. Identifies the main types of seawall or revetment systems, decribes the main prediction methods used to design seawall or revetment armoring and for the first time offer a simple methode to compare design thickness of deferent system. On the field design of seawall or revetment be used at Tourism Area, so type of seawall  or revetment and structure be combined architeture. This Paper is case study Pasir Mayang